Engineering design and static load test of Soil filling pile with spiral cone foundation. Issue 1 (March 2021) - Jin, Zhengchao; Fang, Guangxiu; Zhao, Shifan
Abstract: This paper introduces the innovative soil filling pile with spiral cone technology, and through the soil filling pile with spiral cone foundation static load detection of phase 4 project of Bishui Gardens, Yanji City, Jilin Province, proposed the following design suggestions: When the diameter of the pile is 500mm, the length of the pile is 12-20m, the maximum settlement interval is 28.04 ∼ 44.85mm; the vertical ultimate bearing capacity of single pile is 3600∼4000KN. The pile can speed up the construction period, ensure the project quality and reduce the project cost. It has obvious technical advantages and has obtained good economic and social benefits. It is a new type of energy-saving and emission-reduction pile foundation with extensive application prospects.